Humane health care for prisoners: ethical and legal challenges - Faiver, Kenneth L. (Praeger, 2017)
Ethics in the context of correctional health -- Areas of significant ethical role conflict -- Other challenging topics in ethics -- Legal issues in correctional health care -- How much health care is appropriate and necessary? -- Conceptualizing mental illness as a chronic condition -- A patient or a prisoner? -- Organizing correctional health care -- Corrections and health care working together